Digital Marketing Capability as a Strategic Driver of Competitive Positioning in Indonesian Shipping Companies: An Operational Excellence Perspective - Larsen Barasa; Marihot Simanjuntak; April Gunawan Malau; Ahmad Wahid (Fundamental and Applied Management Journal, 2026)
The integration of digital marketing capabilities into strategic management frameworks represents a critical yet underexplored dimension of competitive positioning in maritime transportation. This study examines how Indonesian shipping companies leverage digital marketing strategies — including social media engagement, platform-based logistics marketing, and digital branding — as instruments of strategic decision-making to improve market share and service differentiation. Drawing on dynamic capabilities theory and operational excellence frameworks, the study employs a qualitative research design involving semi-structured interviews with 25 key informants across eight Indonesian shipping companies. Thematic analysis, cross-group comparison, and narrative synthesis were applied to examine patterns across executive, marketing, and operational perspectives. Findings reveal four principal capability dimensions: digital channel integration, data-driven customer engagement, brand differentiation through digital platforms, and performance-aligned digital communication. Critically, competitive positioning gains are most pronounced when digital marketing capabilities are embedded within operational excellence structures, particularly in firms that align digital communication strategies with balanced scorecard or performance management systems. The study contributes a contextually grounded framework for digital marketing capability development in emerging-market maritime firms, with practical implications for industry managers, policymakers, and institutional stakeholders in Indonesia's sea transportation sector.